2011
DOI: 10.1186/1471-2105-12-s3-s6
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning with naturally labeled data for identifying abbreviation definitions

Abstract: BackgroundThe rapid growth of biomedical literature requires accurate text analysis and text processing tools. Detecting abbreviations and identifying their definitions is an important component of such tools. Most existing approaches for the abbreviation definition identification task employ rule-based methods. While achieving high precision, rule-based methods are limited to the rules defined and fail to capture many uncommon definition patterns. Supervised learning techniques, which offer more flexibility i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Nonetheless, further research has shown that higher performances can be reached by applying machine-learning solutions either for the acronyms alone (BioADI, up to 90%) or the pairs composed of the abbreviation and its long-form (up to 91% for Ab3P; 91.4% from Yeganova et. al), which was not relevant for our rather limited experiments [46]-[48].…”
Section: Methodsmentioning
confidence: 89%
“…Nonetheless, further research has shown that higher performances can be reached by applying machine-learning solutions either for the acronyms alone (BioADI, up to 90%) or the pairs composed of the abbreviation and its long-form (up to 91% for Ab3P; 91.4% from Yeganova et. al), which was not relevant for our rather limited experiments [46]-[48].…”
Section: Methodsmentioning
confidence: 89%
“…These rules were developed using an approximate precision measure and are adapted to the length of the abbreviation. NatLAb was developed using machine learning on a naturally labeled training set using potential definitions and random analogs ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…The updated collection class object can be saved in XML format, ready to be accessed by another BioC application. The Perl BioC module has been successfully used by the NatLAb abbreviation system ( 6 ) to make it BioC compatible ( 7 ).…”
Section: Swig: a Bioc C++ Wrapper For Perl And Pythonmentioning
confidence: 99%